SALAT DAN KESEHATAN PERSPEKTIF HUKUM ISLAM - Siti Halimang (Zawiyah: Jurnal Pemikiran Islam, 2016)
Solat is worship which contains some utterances and action started by recitation of laudation and ended by peace be unto you. Solat is worship demanding concentration and absorbed deeply.  Humble before God in Solat can impact to concentration and health mind. If mind is health, all aspect of body will feel health. When Solat all aspect of healthy will be synergy harmoniously. Solat is related to healthy through eacht solat actions that stimulate nerve system, such as back, armpit, shoulder, arm and leg, thigh and finger leg. If all the nerve cencors is stimulated, it will react to certain organ in the body. In perspective of ilamic law this is preventive action to take care of soul, because the purpose of Islamic law is to give commonly useful benefit to soul as the instrument of worship to Allah swt.